Non-phenolic type environment-friendly sizing solution for fiber skeleton material
Patent Information
- Application Number
- CN202211156741.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-09-22
AI Technical Summary
上述技术方案中,同样存在胶乳/橡胶与粘合树脂之间作用力不佳的问题
[0053]本申请浸胶液中的含硫活性化合物能够通过环氧开环反应或硅氧烷取代反应与非酚醛型环保粘合树脂中的羧基、羟基、酸酐、环氧等基团发生化学键合,同时通过硫键与橡胶发生化学键合。因此,本申请能够提高浸胶粘合树脂与胶乳和与橡胶之间的作用强度,最终达到提高整体粘合力的效果。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure BDA0003859091520000031
Abstract
Description
Technical Field
[0001] This application belongs to the field of impregnation liquid technology, specifically relating to a non-phenolic environmentally friendly impregnation liquid for fiber skeleton materials. Background Technology
[0002] In rubber products, fiber-reinforced reinforcing materials primarily function to bear loads and maintain dimensional stability. Their adhesion to rubber plays a decisive role in the performance and lifespan of the rubber products. Common applications include conveyor belts, tires, and hoses. Commonly used reinforcing materials include metals, cellulose, nylon, and polyester.
[0003] For polyester backbone materials, due to the significant differences in polarity and rigidity between polyester fibers and the rubber matrix, an impregnation process is needed to create an impregnated layer to improve the interfacial adhesion between the two phases. Current mainstream impregnation systems are mostly RFL (resorcinol-formaldehyde) systems, where R is resorcinol, F is formaldehyde, and L is latex. This is a composite impregnation emulsion formed by the condensation polymerization of resorcinol and formaldehyde to form a phenolic resin, with the latex encapsulated within. This RFL system primarily bonds to the fibers through the intermolecular forces of RF, and crosslinks with the rubber through the co-vulcanization of the latex and the reaction of residual hydroxymethyl groups in the RF resin with the rubber. For nylon containing a large number of amide bonds, only a small amount of RF is needed to generate a large number of intermolecular forces, such as hydrogen bonds; therefore, single-bath RFL can achieve satisfactory bonding results. However, for polyester materials such as polyethylene terephthalate (PET), the lack of surface groups capable of generating intermolecular forces such as hydrogen bonds makes it difficult to achieve satisfactory bonding results. In industry, a two-bath impregnation method is generally used, that is, epoxy-isocyanate is used as the first bath, and then RFL is used as the second bath.
[0004] The aforementioned RFL impregnation system has two main drawbacks. First, the two-stage impregnation and drying process increases the number of steps and energy consumption, weakening PET's cost advantage over other materials such as nylon. Second, since resorcinol and formaldehyde are both highly toxic substances, the aforementioned impregnation is facing increasingly stringent regulatory restrictions. Furthermore, various occupational safety measures are required in the production and use of the aforementioned impregnation, as well as impregnated cord products, to reduce adverse health effects on workers.
[0005] To address the problems of existing RFL impregnation systems, research has been conducted on various approaches, including one-bath impregnation and alternatives to RF adhesive resins. Broadly speaking, there are two main technical routes. One is a phenolic-based environmentally friendly impregnation system, which uses other phenols and aldehydes to replace resorcinol and formaldehyde. The other is a non-phenolic-based environmentally friendly impregnation system, which uses epoxy, acrylic resin, polyurethane, isocyanate, and other components to create the adhesive formulation, fundamentally eliminating the use of phenols and aldehydes. Typical examples of these two mainstream technical routes are listed below:
[0006] Typical examples of phenolic resin systems include Milliken's patent document US8247490B1 and Michelin's patent document US9840644B2, which propose a series of technical solutions using different phenols, aldehydes, and pre-condensed phenolic resins to replace resorcinol and formaldehyde. These solutions avoid the use of the two toxic materials, resorcinol and formaldehyde. However, the alternative phenols and aldehydes used are often expensive, and the properties of the impregnated layer are inferior to those of resorcinol-formaldehyde resin. Furthermore, using other phenols and aldehydes often only reduces toxicity, with limited improvement in environmental protection.
[0007] For non-phenolic systems, there are several typical technical routes, represented by the following literature.
[0008] Honeywell's patent document US6780922B2 and Pirelli's patent document EP2931808A1 employ epoxy resin to completely replace resorcinol-formaldehyde resin as the adhesive resin in the impregnation system. However, besides the physical differences between the epoxy system and RF, these solutions also suffer from poor adhesion between the adhesive resin and the rubber / latex. Therefore, these systems are rarely used in impregnation to date.
[0009] BFGoodrich's patent document US4472763A, Bridgestone's patent document US9394647B2, and Taiji's patent document CN106084362B all employ a system of epoxy and isocyanate compounded as the adhesive resin. However, these solutions also suffer from poor adhesion between the latex / rubber and the adhesive resin.
[0010] Currently, the main problems with non-phenolic impregnation systems, besides the difference in physical properties between the adhesive resin itself and phenolic adhesive resins, also include the lack of bonding force between the adhesive resin and the rubber / latex, which limits their further development and application. Therefore, there is an urgent need to develop a non-phenolic environmentally friendly impregnation solution for fiber-reinforced materials to address the issue of low bonding force between the adhesive resin and the latex / rubber, thereby enhancing the performance of non-phenolic impregnation systems. Summary of the Invention
[0011] In view of the shortcomings or deficiencies of the prior art, the technical problem to be solved by this application is to provide a non-phenolic environmentally friendly impregnation solution for fiber skeleton materials.
[0012] To solve the above-mentioned technical problems, this application provides the following technical solution:
[0013] This application discloses a non-phenolic environmentally friendly impregnation solution for fiber skeleton materials, comprising: a one-bath impregnation solution suitable for a one-bath impregnation method or a second impregnation solution suitable for a two-bath impregnation method; the solid content of the one-bath impregnation solution is 8% to 45%, and its dry weight comprises: 15% to 70% non-phenolic environmentally friendly adhesive resin, 20% to 70% latex, and 3% to 20% sulfur-containing active compounds; the solid content of the second impregnation solution is 8% to 45%, and its dry weight comprises: 10% to 60% non-phenolic environmentally friendly adhesive resin, 30% to 90% latex, and 3% to 20% sulfur-containing active compounds.
[0014] Furthermore, the solid content of the one-bath impregnation solution is 15% to 35%, and its dry weight includes: 30% to 70% non-phenolic environmentally friendly adhesive resin, 20% to 60% latex, and 5% to 15% sulfur-containing active compounds.
[0015] Furthermore, the solid content of the second impregnation solution is 15% to 35%, and its dry weight includes: 20% to 50% non-phenolic environmentally friendly adhesive resin, 50% to 80% latex, and 5% to 15% sulfur-containing active compounds.
[0016] Furthermore, the one-bath impregnation solution and / or the second impregnation solution further include: additives with a total proportion of less than or equal to 10%; the additives include: pH adjusters, surfactants, film-forming agents, antioxidants and / or crosslinking catalysts.
[0017] Furthermore, the sulfur-containing active compound includes: a first compound and / or a second compound;
[0018] The general structural formula of the first compound is as follows:
[0019]
[0020] In the above formula, m is a positive integer, and the sum of n and k is greater than or equal to 1;
[0021] The general structural formula of the second compound is as follows:
[0022]
[0023] In the above formula, X is a hydrogen atom, or R1, or -R1-Si(R2) )b (OR3) a The sum of a and b is 3, and c is a positive integer.
[0024] Furthermore, m is 1 to 2.
[0025] Furthermore, n is 1 to 4, and n is preferably 1 to 2.
[0026] Furthermore, k is 1 to 4, and k is preferably 1 to 2.
[0027] Furthermore, c is 1 to 3, and c is preferably 1.
[0028] Furthermore, 'a' is 3.
[0029] Further, R, R', and R1 each comprise: an unsubstituted or branched alkyl chain, or an unsubstituted or branched alkenyl chain, or an unsubstituted or branched alkynyl chain, or an unsubstituted or branched heterochain, or an unsubstituted or branched cycloalkyl chain, or an unsubstituted or branched cyclic heterochain, or an unsubstituted or branched cyclic chain containing double bonds, or an unsubstituted or branched cyclic chain containing triple bonds. Alternatively, unsubstituted or branched benzene, or unsubstituted or branched fused ring, or unsubstituted or branched heterocycle; the heterochain is a carbon chain containing oxygen atoms, a carbon chain containing nitrogen atoms, and / or a carbon chain containing sulfur atoms; the heterocycle includes: pyridine, thiophene, or furan; the branch includes: alkyl chain, alkenyl chain, alkynyl chain, heterochain, cycloalkyl chain, cyclic heterochain, cyclic chain containing double bonds, cyclic chain containing triple bonds, benzene, fused ring, and / or heterocycle.
[0030] Furthermore, R, R', and R1 each include: -(CH2) e -O(CH2CH2O) d -(CH2) e -, d is 1~4, e is 1~2; or, C1~C 10 Carbon chain; or, aromatic nucleus structure with 1 to 2 aromatic rings.
[0031] Furthermore, when n is zero, R also includes: independent hydrogen atoms; when k is zero, R' also includes: independent hydrogen atoms.
[0032] Furthermore, the alkyl chain, the alkenyl chain, the alkynyl chain, the heterochain, the cycloalkyl chain, the cyclic heterochain, the cyclic double-bonded chain, the cyclic triple-bonded chain, the benzene, the fused ring, and the heterochain have substituents, the substituents including: hydroxyl, carboxyl, alkoxy, amino, halogen, ester, and / or amide groups.
[0033] Furthermore, R has 6 or fewer carbon atoms.
[0034] Furthermore, when the number of carbon atoms in R is greater than or equal to 5, the mass fraction of heteroatoms is greater than or equal to 15% to ensure the hydrophilicity of R.
[0035] Furthermore, R1 is CH2-CH2-CH2.
[0036] Furthermore, R2 and R3 each comprise: C1 to C2 alkyl groups, and R2 or R3 has R4 substitution; said R4 comprises: hydroxyl, carboxyl, carboxylate, sulfonic acid, sulfonate, thiosulfate, thiosulfate and / or amino.
[0037] Further, the latex includes: styrene-butadiene latex, styrene-butadiene-pyridine latex, butyl-butadiene-pyridine latex, vinylpyridine latex, nitrile latex, hydrogenated nitrile latex, polybutadiene latex, chloroprene latex and / or natural latex.
[0038] Further, the styrene-butadiene latex comprises: styrene-butadiene latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the styrene-butadiene pyridine latex comprises: styrene-butadiene pyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the nitrile butadiene latex comprises: nitrile butadiene pyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the vinylpyridine latex comprises: vinylpyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; the nitrile butadiene latex comprises: nitrile butadiene pyridine latex end-capped with carboxyl groups, hydroxyl groups, acid anhydride, and / or grafted modified; The hydrogenated nitrile butadiene latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified hydrogenated nitrile butadiene latex; the polybutadiene latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified polybutadiene latex; the chloroprene latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified chloroprene latex; the natural latex comprises: carboxyl, hydroxyl, anhydride-terminated and / or graft-modified natural latex.
[0039] Furthermore, the non-phenolic environmentally friendly adhesive resin includes at least one of an epoxy structure, an isocyanate structure, and an active proton structure.
[0040] Furthermore, the non-phenolic environmentally friendly adhesive resin can achieve molecular weight growth and even cross-linking through epoxy ring-opening or isocyanate addition reactions during the heat treatment after impregnation, ultimately forming a cross-linked network structure.
[0041] Furthermore, when the non-phenolic environmentally friendly adhesive resin is compounded with the sulfur-containing active compound, in addition to reacting itself to form a polymer, the components of the non-phenolic environmentally friendly adhesive resin also react with the epoxy groups and / or siloxane groups in the sulfur-containing active compound, thereby attaching the sulfur-containing active compound to the main chain via chemical bonds.
[0042] Furthermore, the monomers forming the epoxy structure include at least one of the following: glycidyl ethers, phenolic glycidyl ether resins, epoxidized linear phenolic resins, glycidyl ester resins, glycidyl amine resins, epoxidized olefin resins with hydrophilic groups, and glycidyl.
[0043] Furthermore, the monomers forming the epoxy structure include one or more of the following: ethylene glycol, propylene glycol, butanediol, glycerol, 2-hydroxymethyl-1,3-propanediol, trimethylolethane, pentaerythritol, sorbitol, or xylitol, as well as mono- or poly-glycidyl ethers.
[0044] Furthermore, the monomers forming the epoxy structure also include: glycidyl, diglycidyl ether, glycidyl methyl ether and / or glycidyl ethyl ether.
[0045] Further, the isocyanate structure includes: diphenylmethane-4,4'-diisocyanate (MDI), toluene diisocyanate (TDI), polymethylene polyphenyl polyisocyanate (PAPI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), 1,6-hexane diisocyanate (HDI), isophorone diisocyanate (IPDI) and / or diphenylmethane diisocyanate (PPDI).
[0046] Furthermore, the isocyanate structure is protected by a blocking agent to maintain its stability in aqueous solution.
[0047] Furthermore, the structure of the blocking agent includes: alcohols, phenols, β-dicarbonyl compounds, oximes, and / or amides.
[0048] Furthermore, the active proton structure includes: acrylic resins, maleic anhydride graft polymers, diamines, diamines, polyamines, polyamines, oligopolyesters, oligomeric amides, and / or polyurethane oligomers.
[0049] Furthermore, the active proton structure also includes: carbon chain polymers with carboxyl-terminated ends and / or carbon chain polymers with hydroxyl-terminated ends, such as carboxyl-terminated polybutadiene or hydroxyl-terminated polybutadiene.
[0050] Furthermore, the active proton structure also includes: diols and / or polyols, such as polyester polyols or polyether polyols.
[0051] Furthermore, the active proton structure also includes polymers containing hydroxyl side groups, such as polyvinyl alcohol.
[0052] Compared with the prior art, this application has the following technical effects:
[0053] The sulfur-containing active compounds in the impregnation solution of this application can chemically bond with carboxyl, hydroxyl, acid anhydride, epoxy, and other groups in non-phenolic environmentally friendly adhesive resins through epoxy ring-opening reactions or siloxane substitution reactions, and simultaneously chemically bond with rubber through sulfur bonds. Therefore, this application can improve the interaction strength between the impregnated adhesive resin and latex and with rubber, ultimately achieving the effect of improving overall adhesion.
[0054] The methods for synthesizing sulfur-containing active compounds in this application are diverse and simple, and their structures are easy to adjust. The molecular structure can be adjusted according to product requirements, which is conducive to further performance improvement and application expansion.
[0055] This application enhances the affinity between the impregnation layer and the rubber layer in the non-phenolic impregnation method, which is beneficial to improving the adhesion index of the impregnated cord, facilitating the implementation of the one-bath impregnation method, avoiding the large energy consumption caused by the two-bath impregnation process, effectively improving production efficiency and reducing production costs. Of course, this application can also be used in the second impregnation of the two-bath impregnation method to improve the adhesion between the cord and the rubber.
[0056] Compared to other traditional RF formulations, this application avoids the addition of toxic and harmful phenolic substances. Compared to existing one-bath impregnation formulations, this application can generate chemical cross-links between the impregnating material and the rubber during the impregnation process, achieving a better bonding effect.
[0057] This application has good compatibility with traditional dipping solutions in terms of equipment and processes, which is beneficial for factories to organize production and switch between different product categories. Detailed Implementation
[0058] The following embodiments further illustrate this application, but the implementation and protection of this application are not limited thereto. It should be noted that any processes not specifically described below are methods that can be implemented or understood by those skilled in the art by referring to existing technology. Reagents or instruments whose manufacturers are not specified are considered to be conventional products that can be purchased commercially.
[0059] The reagents used in Examples 1 to 7 below:
[0060] Deionized water: homemade;
[0061] Ethyl acetate: distillation grade, Adamas;
[0062] Nano sulfur dispersion: 10%, Shanghai Huzheng;
[0063] Sodium sulfide nonahydrate: AR, 98%, general reagent (GReagent');
[0064] Methanol: Sinopharm, AR, 99%;
[0065] m-chloroperoxybenzoic acid (mCPBA), Adamas;
[0066] Sulfoxide dichloride: AR, 98%, Adamas;
[0067] N,N-Dimethylformamide (DMF): AR, 99%, Adamas;
[0068] Ethylene glycol: Industrial grade, with a purity of 99.5% as determined by quality inspection, and a water content of 0.04% as determined by the Karl Fischer method;
[0069] Sulfuric acid: AR, 98%;
[0070] Lactic acid: AR, 90%, after being dehydrated by distillation and then dried in two steps with anhydrous sodium sulfate and 3A molecular sieve;
[0071] Ether-chain epoxy precursor: self-made, specifically starting from 2-allyl hydroxyethyl ether, through two reaction steps of thionyl chloride chlorination and epoxidation, to obtain the precursor 2-epoxy-2'-chloroethyl ether, the structure of which is shown below:
[0072]
[0073] Aromatic epoxy precursor: self-made, specifically obtained by epoxidation of p-chloromethylstyrene with mCPBA, as shown below:
[0074]
[0075] JH-S69 - Industrial grade, manufactured by Hubei Jianghan Organosilicon, structure is shown below:
[0076]
[0077] JH-S75 - Industrial Grade, manufactured by Hubei Jianghan Organosilicon, structure is shown below:
[0078]
[0079] This application discloses a non-phenolic environmentally friendly impregnation solution for fiber skeleton materials, comprising: a one-bath impregnation solution suitable for a one-bath impregnation method or a second impregnation solution suitable for a two-bath impregnation method; the solid content of the one-bath impregnation solution is 8% to 45%, and its dry weight comprises: 15% to 70% non-phenolic environmentally friendly adhesive resin, 20% to 70% latex, and 3% to 20% sulfur-containing active compounds; the solid content of the second impregnation solution is 8% to 45%, and its dry weight comprises: 10% to 60% non-phenolic environmentally friendly adhesive resin, 30% to 90% latex, and 3% to 20% sulfur-containing active compounds.
[0080] When the solid content is below 8%, the impregnation solution contains too much water and too little adhesive, resulting in poor adhesion; when the solid content is above 45%, the impregnation solution has poor stability and high viscosity, making operation difficult.
[0081] Preferably, the solid content is 20% to 30%.
[0082] This application can improve the interaction strength between the impregnating adhesive resin and the latex and rubber, thereby improving the overall adhesive strength. Compared with other traditional RF formulations, this application avoids the addition of toxic and harmful phenolic substances; compared with existing one-bath impregnation method formulations, this application can generate chemical cross-linking between the impregnating resin and the rubber during the impregnation process, achieving a better adhesive effect. Specific embodiments are provided below for illustration.
[0083] Example 1
[0084] The sulfur-containing active compound has the following chemical structure, namely compound A:
[0085]
[0086] The specific preparation process of compound A is as follows:
[0087] Take 240g of sodium sulfide nonahydrate, add 320g of 10% nano sulfur solution, and stir at room temperature under nitrogen protection until the solution becomes clear to obtain sodium sulfide solution.
[0088] The sodium persulfide solution has a mass fraction of approximately 20%.
[0089] Take 150g of epichlorohydrin into a 500ml round-bottom flask, cool it to 5℃ in an ice-water bath, and add 50g of 20% sodium persulfate solution dropwise. After the addition is complete, continue stirring in the ice-water bath for 2 hours until the orange-yellow color of sodium persulfate completely disappears.
[0090] The reaction mixture was diluted with 100 mL of saturated brine and extracted with 200 mL of ethyl acetate. After separation, the organic phase was retained. The mixture was washed with saturated brine until the pH did not exceed 9, yielding a golden-yellow organic phase. The organic phase was then removed by solvent removal using a rotary evaporator, followed by distillation under high vacuum using an oil pump to remove residual epichlorohydrin, yielding the product. The product was a golden-yellow viscous liquid, and its structure and purity were confirmed by peak area normalization (GC-MS). Specifically, the yield was 13.1 g, with a purity of approximately 92% and a yield of 89%.
[0091] Example 2
[0092] The sulfur-containing active compound has the following chemical structure, namely compound B:
[0093]
[0094] The specific preparation process of compound B is as follows:
[0095] 200 g of the ether-chain epoxy precursor compound was placed in a 1000 ml round-bottom flask and cooled to 5 °C in an ice-water bath. 50 g of the 20% sodium persulfide solution described in Example 1 was added dropwise over 3 hours. The reaction mixture was stirred in the ice-water bath for another 2 hours until the orange-yellow color of the sodium persulfide essentially disappeared. After the reaction was complete, the reaction mixture was diluted with saturated brine and extracted with ethyl acetate. The extracted organic phase was washed with saturated brine until the pH was no higher than 9, yielding a golden-yellow organic phase. After removing the solvent from this organic phase using a rotary evaporator, it was distilled under high vacuum using an oil pump to remove the residual ether-chain epoxy precursor compound, yielding the product. The product was a golden-yellow viscous liquid, and its structure and purity were confirmed by GC-MS. Specifically, the yield was 17.9 g, with a purity of approximately 85% and a yield of 71%.
[0096] Example 3
[0097] The sulfur-containing active compound has the following chemical structure, namely compound C:
[0098]
[0099] The specific preparation process of compound C is as follows:
[0100] 200 g of the aromatic epoxy precursor compound was placed in a 1000 ml round-bottom flask and cooled to 5 °C in an ice-water bath. 50 g of the 20% sodium persulfide solution described in Example 1 was added dropwise over 3 hours. The reaction mixture was stirred in the ice-water bath for another 3 hours until the orange-yellow color essentially disappeared. After the reaction was complete, the reaction mixture was diluted with saturated brine and extracted twice with ethyl acetate. The extracted organic phase was washed with saturated brine until the pH was no higher than 9, yielding a yellow organic phase. The organic phase was then subjected to a high vacuum distillation using an oil pump to remove residual aromatic epoxy precursor compounds, yielding the product. The product was a golden-yellow viscous liquid, and its structure and purity were confirmed by GC-MS. Specifically, the yield was 27 g, with a purity of approximately 81% and a yield of 76%.
[0101] Example 4
[0102] The sulfur-containing active compound has the following chemical structure, namely compound D:
[0103]
[0104] The specific preparation process of compound D is as follows:
[0105] 48g of JH-S75 coupling agent, 62g of ethylene glycol, and 100mg of concentrated sulfuric acid were placed in a 250ml round-bottom flask, which was connected to a vacuum distillation apparatus. At room temperature, the ethylene glycol and silane coupling agent separated into two layers, and after thorough stirring, a turbid emulsion was obtained. The reaction mixture was heated to 80°C, and a circulating water vacuum pump was used to reduce the pressure. At this point, the reaction mixture began to boil, and liquid condensed in the distillation condenser. As the reaction proceeded, the liquid phase gradually became clear and transparent, and then the viscosity increased. This colorless, clear, viscous liquid is compound D. 2g of compound D was dispersed in 50ml of deionized water, and the product was found to be a homogeneous emulsion that remained stable after stirring was stopped. The product was characterized by 1H NMR spectroscopy, revealing that the residual ethoxy groups were 0.81 per silicon atom.
[0106] Example 5
[0107] The sulfur-containing active compound has the following chemical structure, namely compound E:
[0108]
[0109] The specific preparation process of compound E is as follows:
[0110] 54g of JH-S69 coupling agent, 62g of ethylene glycol, and 100mg of concentrated sulfuric acid were placed in a 250ml round-bottom flask, which was connected to a vacuum distillation apparatus. At room temperature, the ethylene glycol and silane coupling agent separated into two layers, and after thorough stirring, a turbid emulsion was obtained. The reaction mixture was heated to 80°C, and a circulating water vacuum pump was used to reduce the pressure. At this point, more boiling occurred in the reaction mixture, and liquid condensed and precipitated in the distillation condenser. As the reaction proceeded, the liquid phase gradually became basically clear and transparent, and then the viscosity increased. This light yellow, clear, viscous liquid is compound E. 2g of compound E was dispersed in 50ml of deionized water, and the product was found to be a homogeneous emulsion that remained stable after stirring was stopped. The product was characterized by 1H NMR spectroscopy, revealing that the residual ethoxy groups were 0.95 per silicon atom.
[0111] Example 6
[0112] The sulfur-containing active compound has the following chemical structure, namely compound F:
[0113]
[0114] The specific preparation process of compound F is as follows:
[0115] 200g of 90% lactic acid was distilled to remove approximately 12g of water and then dissolved in 400g of anhydrous ethanol to prepare a solution. After drying using a 3A molecular sieve and sodium sulfate, the ethanol was removed by rotary evaporation to obtain dry lactic acid. 60g of the dried lactic acid was mixed with 48g of JH-S75 coupling agent in a 250ml flask, heated to 60℃, and the ethanol was removed under vacuum. After reacting for 4 hours, the mixture was cooled to room temperature to obtain a white solid compound F. Compound F was characterized by 1H NMR spectroscopy, revealing a residual ethoxy group of 0.41 per silicon atom.
[0116] Example 7
[0117] The sulfur-containing active compound has the following chemical structure, namely compound G:
[0118]
[0119] The specific preparation process of compound G is as follows:
[0120] 200g of 90% lactic acid was dissolved in 400g of anhydrous ethanol to prepare a solution. After drying using a 3A molecular sieve and sodium sulfate, the ethanol was removed by rotary evaporation to obtain dry lactic acid. 19g of the dried lactic acid was mixed with 48g of JH-S75 coupling agent in a 125ml flask, heated to 60℃, and the ethanol was removed under vacuum. After reacting for 4 hours, the mixture was cooled to room temperature to obtain a white solid compound G. The product was characterized by 1H NMR spectroscopy, which revealed that it contained 2.0 residual ethoxy groups per silicon atom.
[0121] The reagents used in Examples 8 to 36 and Comparative Examples 1 to 11 are as follows:
[0122] Latex includes:
[0123] Butadiene-pyridine latex (VP): Commercially available, 40%;
[0124] Styrene-butadiene rubber latex (SBR): Commercially available, 40%;
[0125] Natural latex (NR): Commercially available, 40%;
[0126] Carboxylated styrene-butadiene latex (XSBRL45B): Commercially available, 50%.
[0127] Non-phenolic environmentally friendly adhesive resins include:
[0128] Acrylic latex: Commercially available acrylic (ACD) slurry, solid content 20%;
[0129] Epoxy EX614B: Available in Nagase, ready to use;
[0130] Epoxy EX512: Available in Nagase, ready to use;
[0131] Epoxy G1701: EMS-Griltech, Switzerland, ready to use;
[0132] Grilbond IL6, a 60% isocyanate emulsion, is available from EMS-Griltech, Switzerland, ready to use.
[0133] PET cord: Hailide Company, 1000D.
[0134] Example 8
[0135] The specific preparation process of the non-phenolic environmentally friendly impregnation solution in this embodiment is as follows, and the specific addition amount is referenced in Table 1:
[0136] Deionized water was weighed into a three-necked flask, and a magnetic stir bar was added. Then, while stirring, epoxy structures were added. In this embodiment, the epoxy structures used were epoxy EX614B and epoxy G1701. After epoxy EX614B and epoxy G1701 dispersed, additives and active components were added. In this embodiment, the additive was ammonia, and the active component was compound A. Then, blocked isocyanate emulsion IL6 was added. After stirring evenly, latex was added. In this embodiment, the latex was butadiene-pyridine latex (VP). After stirring evenly, a non-phenolic environmentally friendly impregnating solution was obtained.
[0137] The impregnation test process in this embodiment is as follows:
[0138] The PET cords were impregnated using a single-line impregnation machine. The PET cords were impregnated in each impregnation tank for approximately 8 seconds. After each impregnation, the PET cords were dried in a first oven at 170°C and then cured in a second oven at 240°C. The residence time in each oven was approximately 2 minutes. The tension of the PET cords was maintained between 4.0 and 5.0 N during impregnation and drying. In the impregnation machine, the first impregnation tank used the impregnation solution produced by the existing D417 first bath formulation, and the second impregnation tank used the non-phenolic environmentally friendly impregnation solution produced in this embodiment. The dried and cured PET cords exhibited a color ranging from white to light yellow.
[0139] The impregnated cords obtained by the above method were subjected to CRA peel tests using the test method of GB / T40725-2021. The total peel force of the five cords and the grade of rubber coating on the cord surface were recorded, denoted as grades A to E. In this embodiment, the CRA peel force of the impregnated cord was 151.66 N, and the amount of rubber adhering to the peeled surface was determined to be grade A.
[0140] Example 9
[0141] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 1. After the impregnation test, the CRA peel strength of the impregnated cord was 146.24 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0142] Example 10
[0143] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the amount of compound A added in this embodiment is the upper limit of the amount of compound A added in this application. The amount added is detailed in Table 1. After the impregnation test, the CRA peel strength of the impregnated cord was 166.50 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0144] Example 11
[0145] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound D. The amount of compound D added in this embodiment is the upper limit of the amount of compound D added in this application. The amount added is detailed in Table 1. After the impregnation test, the CRA peel strength of the impregnated cord was 150.39 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0146] Example 12
[0147] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the amount of compound A added in this embodiment is the upper limit of the amount of compound A added in this application. The amount added is detailed in Table 1. After the impregnation test, the CRA peel strength of the impregnated cord was 141.15N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0148] Example 13
[0149] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound D. The amount of compound D added in this embodiment is the lower limit of the amount of compound D added in this application. The amount added is detailed in Table 1. After the impregnation test, the CRA peel strength of the impregnated cord was 137.07 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0150] Example 14
[0151] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 9 is that the amounts of epoxy EX614B, epoxy G1701, blocked isocyanate emulsion IL6, and VP added in this embodiment are different. The specific amounts added are detailed in Table 1. After the impregnation test, the CRA peel strength of the impregnated cord was 135.94N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0152] Example 15
[0153] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the amounts of epoxy EX614B, epoxy G1701, blocked isocyanate emulsion IL6, and VP added in this embodiment are different. The specific amounts added are detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 100.41N, and the amount of adhesive adhering to the peel surface was judged to be Grade A.
[0154] Example 16
[0155] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that styrene-butadiene rubber was added to the latex in this embodiment. The specific amount added is detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 142.34 N, and the amount of adhesive adhering to the peel surface was judged to be Grade A.
[0156] Example 17
[0157] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 16 is that the active component added in this embodiment is compound D. The amount of compound D added in this embodiment is the lower limit of the amount of compound D added in this application. The amount added is detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 138.68 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0158] Example 18
[0159] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the additive added in this embodiment is sodium hydroxide, and the specific amount added is detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 154.49 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0160] Example 19
[0161] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 9 is that the additive added in this embodiment is sodium hydroxide, and the specific amount added is detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 147.02 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0162] Example 20
[0163] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound B, and the amount added is detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 145.76 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0164] Example 21
[0165] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound C, and the amount added is detailed in Table 2. After the impregnation test, the CRA peel strength of the impregnated cord was 142.08 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0166] Example 22
[0167] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound E, and the amount added is detailed in Table 3. After the impregnation test, the CRA peel strength of the impregnated cord was 136.69 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0168] Example 23
[0169] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound F, and the amount added is detailed in Table 3. After the impregnation test, the CRA peel strength of the impregnated cord was 133.03 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0170] Example 24
[0171] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 8 and completed the impregnation test. The difference from Example 8 is that the active component added in this embodiment is compound G, and the amount added is detailed in Table 3. After the impregnation test, the CRA peel strength of the impregnated cord was 129.84 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0172] Example 25
[0173] The specific preparation process of the non-phenolic environmentally friendly impregnation solution in this embodiment is as follows, and the specific addition amount is referenced in Table 4:
[0174] Deionized water was weighed into a three-necked flask, a magnetic stir bar was added, carboxylated styrene-butadiene latex was added, followed by ammonia water while stirring, then blocked isocyanate emulsion IL6 and the active component. In this embodiment, the active component is compound A. After stirring evenly, VP latex was added. After stirring evenly, a non-phenolic environmentally friendly impregnating solution was obtained. Using the impregnation test method described in Example 8, the CRA peel strength of the impregnated cord was 112.37 N, and the amount of adhesive adhering to the peel surface was judged to be Grade A.
[0175] Example 26
[0176] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 25 and completed the impregnation test. The difference from Example 25 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 4. After the impregnation test, the CRA peel strength of the impregnated cord was 103.06 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0177] Example 27
[0178] The specific preparation process of the non-phenolic environmentally friendly impregnation solution in this embodiment is as follows, and the specific addition amount is referenced in Table 4:
[0179] Deionized water was weighed into a three-necked flask, and a magnetic stir bar was added. Then, acrylic latex and ammonia were added while stirring. After the latex and ammonia were fully dispersed, the active component and blocked isocyanate emulsion IL6 were added. In this example, compound A was used as the active component. After stirring evenly, VP latex was added. After stirring evenly, a non-phenolic environmentally friendly impregnating solution was obtained. Using the impregnation test method described in Example 8, the CRA peel strength of the impregnated cord was 97.69 N, and the amount of adhesive adhering to the peel surface was judged to be Grade A.
[0180] Example 28
[0181] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 27 and completed the impregnation test. The difference from Example 27 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 4. After the impregnation test, the CRA peel strength of the impregnated cord was 88.24 N, and the amount of adhesive on the peel surface was judged to be grade B.
[0182] Example 29
[0183] The specific preparation process of the non-phenolic environmentally friendly impregnation solution in this embodiment is as follows, and the specific addition amount is referenced in Table 4:
[0184] Deionized water was weighed into a three-necked flask, and a magnetic stir bar was added. Ammonia and the active component (compound A, used in this embodiment) were then added while stirring. Blocked isocyanate emulsion IL6 was then added. After thorough stirring, VP latex was added. The non-phenolic environmentally friendly impregnating solution was obtained after thorough stirring. Using the impregnation test method described in Example 8, the CRA peel strength of the impregnated cord was 84.53 N, and the amount of adhesive residue on the peel surface was classified as Grade B.
[0185] Example 30
[0186] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 29 and completed the impregnation test. The difference from Example 29 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 4. After the impregnation test, the CRA peel strength of the impregnated cord was 79.60 N, and the amount of adhesive on the peel surface was judged to be Grade B.
[0187] Example 31
[0188] The specific preparation process of the non-phenolic environmentally friendly impregnation solution in this embodiment is as follows, and the specific addition amount is referenced in Table 5:
[0189] Deionized water was weighed into a three-necked flask, and a magnetic stir bar was added. Then, carboxylated styrene-butadiene latex was added while stirring, followed by ammonia and the active component. In this embodiment, the active component is compound A. After stirring evenly, VP latex was added. After stirring evenly, a non-phenolic environmentally friendly impregnating solution was obtained. Using the impregnation test method described in Example 8, the CRA peel strength of the impregnated cord was 115.82 N, and the amount of adhesive adhering to the peel surface was determined to be Grade A.
[0190] Example 32
[0191] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 31 and completed the impregnation test. The difference from Example 31 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 5. After the impregnation test, the CRA peel strength of the impregnated cord was 103.44 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0192] Example 33
[0193] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 31 and completed the impregnation test. The difference from Example 31 is that the epoxy structure added in this embodiment is epoxy EX512 and epoxy G1701, and the amount added is detailed in Table 5. After the impregnation test, the CRA peel strength of the impregnated cord was 131.13N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0194] Example 34
[0195] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 33 and completed the impregnation test. The difference from Example 33 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 5. After the impregnation test, the CRA peel strength of the impregnated cord was 122.65 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0196] Example 35
[0197] The specific preparation process of the non-phenolic environmentally friendly impregnation solution in this embodiment is as follows, and the specific addition amount is referenced in Table 5:
[0198] Deionized water was weighed into a three-necked flask, and a magnetic stir bar was added. Then, while stirring, epoxy structure, ammonia, acrylic latex, and active component were added sequentially, followed by blocked isocyanate. In this embodiment, the epoxy structure used is epoxy EX614B and epoxy G1701; the active component is compound A. After stirring evenly, VP latex was added. After stirring evenly, a non-phenolic environmentally friendly impregnating solution was obtained. Using the impregnation test method described in Example 8, the CRA peel strength of the impregnated cord was 121.36 N, and the amount of adhesive adhering to the peel surface was determined to be Grade A.
[0199] Example 36
[0200] This embodiment prepared a non-phenolic environmentally friendly impregnation solution according to the method of Example 35 and completed the impregnation test. The difference from Example 35 is that the active component added in this embodiment is compound D, and the amount added is detailed in Table 5. After the impregnation test, the CRA peel strength of the impregnated cord was 109.32 N, and the amount of adhesive on the peel surface was judged to be Grade A.
[0201] Comparative Example 1
[0202] This comparative example serves as a control over Examples 8 to 13 and Examples 20 to 24 described above. In this comparative example, a non-phenolic environmentally friendly impregnating solution was prepared according to the method of Example 8, and impregnation testing was performed. The difference between this comparative example and the control examples is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 6. The impregnation test in this comparative example yielded a CRA peel strength of 122.57 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade A.
[0203] Comparative Example 2
[0204] This comparative example serves as a control over Example 14 described above. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method in Example 8, and impregnation testing was performed. The difference from Example 14 is that no active component was added in this example, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 6. The impregnation test in this comparative example yielded a CRA peel strength of 104.24 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade A.
[0205] Comparative Example 3
[0206] This comparative example serves as a control over Example 15 described above. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 8, and impregnation testing was performed. The difference from Example 15 is that no active component was added in this example, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 6. The impregnation test in this comparative example yielded a CRA peel strength of 87.04 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade B.
[0207] Comparative Example 4
[0208] This comparative example serves as a control over Examples 16 and 17 described above. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method in Example 8, and impregnation testing was performed. The difference between this comparative example and Examples 16 and 17 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 6. The impregnation test in this comparative example yielded a CRA peel strength of 117.02 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade A.
[0209] Comparative Example 5
[0210] This comparative example serves as a control over Examples 18 and 19 described above. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method in Example 8, and impregnation testing was performed. The difference between this comparative example and Examples 18 and 19 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 6. The impregnation test in this comparative example yielded a CRA peel strength of 120.71 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade A.
[0211] Comparative Example 6
[0212] This comparative example serves as a control over Examples 25 and 26. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 25, and impregnation testing was performed. The difference between this comparative example and Examples 25 and 26 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 7. The impregnation test in this comparative example yielded a CRA peel strength of 74.92 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade B.
[0213] Comparative Example 7
[0214] This comparative example serves as a control over Examples 27 and 28. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 27, and impregnation testing was performed. The difference between this comparative example and Examples 27 and 28 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 7. The impregnation test in this comparative example yielded a CRA peel strength of 68.33 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade B.
[0215] Comparative Example 8
[0216] This comparative example serves as a control over Examples 29 and 30. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 29, and impregnation testing was performed. The difference between this comparative example and Examples 29 and 30 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 7. The impregnation test in this comparative example yielded a CRA peel strength of 65.25 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade C.
[0217] Comparative Example 9
[0218] This comparative example serves as a control over Examples 31 and 32 described above. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 31, and impregnation testing was performed. The difference between this comparative example and Examples 31 and 32 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 7. The impregnation test in this comparative example yielded a CRA peel strength of 86.07 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade B.
[0219] Comparative Example 10
[0220] This comparative example serves as a control over Examples 33 and 34. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 33, and impregnation testing was performed. The difference between this comparative example and Examples 33 and 34 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 7. The impregnation test in this comparative example yielded a CRA peel strength of 101.66 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade A.
[0221] Comparative Example 11
[0222] This comparative example serves as a control over Examples 35 and 36. In this comparative example, a non-phenolic environmentally friendly impregnation solution was prepared according to the method of Example 35, and impregnation testing was performed. The difference between this comparative example and Examples 35 and 36 is that no active component was added, i.e., no sulfur-containing active compound was added. Specific addition amounts are shown in Table 7. The impregnation test in this comparative example yielded a CRA peel strength of 91.77 N for the impregnated cord, and the amount of adhesive adhering to the peel surface was classified as Grade A.
[0223] Table 1. Summary of data from Examples 8 to 14
[0224]
[0225]
[0226] Table 2 Summary of data from Examples 15 to 21
[0227]
[0228]
[0229] Table 3. Summary of data from Examples 22 to 28
[0230]
[0231]
[0232] Table 4 Summary of data from Examples 25 to 30
[0233]
[0234]
[0235] Table 5 Summary of data from Examples 31 to 36
[0236]
[0237]
[0238] Table 6 Summary of data from Comparative Examples 1 to 5
[0239]
[0240]
[0241] Table 7 Summary of data from Comparative Examples 6 to 11
[0242]
[0243]
[0244] The above embodiments achieved good results in the one-bath impregnation process. Tests have shown that this application can also achieve the same results in the second impregnation process of the two-bath impregnation process.
[0245] The above embodiments are only used to illustrate the technical solutions of this application and are not intended to limit it. The preferred embodiments have been described in detail. Those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the spirit and scope of the technical solutions of this application, and all such modifications and substitutions should be covered within the scope of the claims of this application.
Claims
1. A non-phenolic environmentally friendly impregnation solution for fiber skeleton materials, characterized in that, include: A one-bath impregnation solution suitable for one-bath impregnation or a second impregnation solution suitable for two-bath impregnation; The solid content of the one-bath impregnation solution is 8% to 45%, and its dry weight includes: 15% to 70% non-phenolic environmentally friendly adhesive resin, 20% to 70% latex and 3% to 20% sulfur-containing active compounds. The second impregnation solution has a solid content of 8% to 45%, and its dry weight includes: 10% to 60% non-phenolic environmentally friendly adhesive resin, 30% to 90% latex and 3% to 20% sulfur-containing active compounds. The sulfur-containing active compound includes: a first compound and / or a second compound; The general structural formula of the first compound is as follows: , In the above formula, m is a positive integer, and the sum of n and k is greater than or equal to 1; The general structural formula of the second compound is as follows: , In the above formula, X is -R1-Si(R2). b (OR3) a The sum of a and b is 3, and c is a positive integer from 1 to 3; R, R', and R1 each include: unsubstituted or branched C1~C1. 10 Alkyl chain, or unsubstituted or branched heterochain, said heterochain being a carbon chain containing oxygen atoms, or unsubstituted or branched benzene; The branched chain includes: alkyl chain; R2 and R3 each comprise: C1~C2 alkyl groups, and R2 or R3 has R4 substitution; The R4 group includes a hydroxyl group or a carboxyl group.
2. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to claim 1, characterized in that, The solid content of the one-bath impregnation solution is 15% to 35%, and its dry weight includes: 30% to 70% non-phenolic environmentally friendly adhesive resin, 20% to 60% latex, and 5% to 15% sulfur-containing active compounds.
3. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to claim 1, characterized in that, The second impregnation solution has a solid content of 15% to 35%, and its dry weight includes: 20% to 50% non-phenolic environmentally friendly adhesive resin, 50% to 80% latex and 5% to 15% sulfur-containing active compounds.
4. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to any one of claims 1 to 3, characterized in that, The one-bath impregnation solution and / or the second impregnation solution further include: an auxiliary agent with a total proportion of less than or equal to 10%; The additives include: pH adjusters, surfactants, film-forming agents, antioxidants, and / or crosslinking catalysts.
5. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to any one of claims 1 to 3, characterized in that, The benzene has substituents, including hydroxyl or carboxyl groups.
6. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to any one of claims 1 to 3, characterized in that, The latexes include: styrene-butadiene latex, styrene-butadiene-pyridine latex, butyl pyridine latex, vinyl pyridine latex, nitrile latex, hydrogenated nitrile latex, polybutadiene latex, chloroprene latex, and / or natural latex.
7. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to claim 6, characterized in that, The styrene-butadiene rubber latex includes: styrene-butadiene rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or styrene-butadiene rubber latex grafted with carboxyl, hydroxyl, or anhydride; the styrene-butadiene pyridine rubber latex includes: styrene-butadiene pyridine rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or styrene-butadiene pyridine rubber latex grafted with carboxyl, hydroxyl, or anhydride; the styrene-butadiene pyridine rubber latex includes: styrene-butadiene pyridine rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or styrene-butadiene pyridine rubber latex grafted with carboxyl, hydroxyl, or anhydride; the vinylpyridine rubber latex includes: vinylpyridine rubber latex end-capped with carboxyl, hydroxyl, or anhydride, or vinylpyridine rubber latex grafted with carboxyl, hydroxyl, or anhydride; the nitrile rubber latex includes: nitrile rubber latex end-capped with carboxyl, hydroxyl, or anhydride. The following are types of latex: latex, or nitrile butadiene latex grafted with carboxyl, hydroxyl, and anhydride groups; the hydrogenated nitrile butadiene latex includes: hydrogenated nitrile butadiene latex end-capped with carboxyl, hydroxyl, and anhydride groups, or hydrogenated nitrile butadiene latex grafted with carboxyl, hydroxyl, and anhydride groups; the polybutadiene latex includes: polybutadiene latex end-capped with carboxyl, hydroxyl, and anhydride groups, or polybutadiene latex grafted with carboxyl, hydroxyl, and anhydride groups; the chloroprene latex includes: chloroprene latex end-capped with carboxyl, hydroxyl, and anhydride groups, or chloroprene latex grafted with carboxyl, hydroxyl, and anhydride groups; the natural latex includes: natural latex end-capped with carboxyl, hydroxyl, and anhydride groups, or natural latex grafted with carboxyl, hydroxyl, and anhydride groups.
8. The non-phenolic environmentally friendly impregnation solution for fiber skeleton materials according to any one of claims 1 to 3, characterized in that, The non-phenolic environmentally friendly adhesive resin includes at least one of epoxy structure and isocyanate structure.
Citation Information
Patent Citations
An environment-friendly fiber skeleton material dipping solution and dipping process
CN106084362B
Polyolefin composition
EP2931808A1
Plug-in module card holder
US4472763A
Adhesion promoters with epoxy-reactive groups
US6780922B2
Adhesion composition and textile materials and articles treated therewith
US8247490B1